Proteomic Analysis of Common Bean (Phaseolus vulgaris L.) by Two-Dimensional Gel Electrophoresis and Mass Spectrometry - Savithiry S. Natarajan,; M.A. Pastor-Corrales,; `Farooq H. Khan,; `Wesley M. Garrett, (Journal of Basic & Applied Sciences, 2021)
The modern cultivated common bean (Phaseolus vulgaris) has evolved from wild common beans distributed in Central America, Mexico and the Andean region of South America. It has been reported that wild common bean accessions have higher levels of protein content than the domesticated dry bean cultivars. However, there is limited proteomic analysis of wild or domesticated common beans. In this investigation, we reported a proteomic analysis of a wild bean from Mexico. We utilized the TCA/Acetone method for protein extraction, two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) for protein separation, and subsequent mass spectrometry (MS) for protein identification. Proteins were separated in the first dimension using pH range from 4-7. A total of 237 protein spots from the second dimension were isolated, digested with trypsin, and analyzed by MALDI/TOF/TOF mass spectrometry. We identified 141 protein spots by searching NCBI non redundant databases using the Mascot search engine and found a total of 43 unique proteins. Gene Ontology (GO) analysis was employed to understand the molecular processes in which the identified common bean proteins are involved. The majority of proteins are involved in binding (41.5%) and catalytic activity (35.8%), followed by nutrient reservoir activity (7.5%), antioxidant activity (1.9%), transporter activity (3.8%), enzyme regulator activity (3.8%), structural molecule activity (1.9%), and electron carrier activity (3.8%). The results indicate that TCA/Acetone extraction and 2D-PAGE is efficient in separating common bean proteins. Further identification of these proteins by MS demonstrates the quality of this protein extraction method. These results will be useful for the development of value added common beans by alteration of protein components.